Perbandingan Waktu Pencapaian Bromage Score 3 Pada Pasien Hipertensi ASA II-III Pasca Spinal Anestesi - Wafiq Aida Qurotul Ain (Indonesian Journal of Health Community, 2026)
Hypertension is one of the most common comorbid conditions found in patients undergoing surgical procedures. In both major and minor surgeries, anesthesia is a crucial stage of perioperative management. Spinal anesthesia is a form of regional anesthesia performed by injecting a local anesthetic agent into the subarachnoid space. This study aimed to determine and compare the mean time required to achieve Bromage Score 3 in ASA II and ASA III patients undergoing spinal anesthesia with a Subarachnoid Block technique. This study employed a quantitative research method, as the data obtained were numerical in nature, specifically the time required to achieve Bromage Score 3. An observational analytic design was used, which is intended to analyze relationships or differences between variables without providing any intervention to the research subjects. The results of the Mann-Whitney test demonstrated a statistically significant difference between the ASA II and ASA III groups in achieving Bromage Score 3, with a p-value of 0.002 (<0.05). The mean rank value in the ASA III group (13.17) was higher than that in the ASA II group (5.85), indicating that the time required to achieve Bromage Score 3 tended to be shorter in ASA II patients than in ASA III patients.